LGBT dalam Perspektif Hukum Islam dan HAM - Dyah Erlina Sulistyaningrum; Suryadi Suryadi; Muhammad Achwan; Maria Yosepin Endah Listyowati; Husin Husin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The presence of LGBT individuals (Lesbian, Gay, Bisexual, and Transgender) in society has raised complex discussions, especially when viewed from the perspectives of Islamic law and human rights. Islamic teachings generally view same-sex relations and gender transitions as actions that deviate from the moral and natural order established by religious texts. In contrast, the human rights framework emphasizes individual dignity, personal freedom, and the right to non-discrimination, regardless of sexual orientation or gender identity. This article seeks to explore the intersection of these two perspectives, not to provoke conflict, but to offer a balanced understanding rooted in empathy, justice, and social awareness. Using a qualitative normative approach, this research examines Islamic legal sources, national regulations, and international human rights documents. The study finds that while Islamic law maintains clear normative boundaries, there is still room for inclusive dialogue and respectful engagement, especially in multicultural societies like Indonesia. Bridging these two frameworks requires not only legal analysis but also cultural sensitivity and ethical responsibility.